SUSTAINABILITY COST ACCOUNTING - PART 2: A CASE STUDY IN THE SOUTH AFRICAN PROCESS INDUSTRY - Brent, A.C.; Van Erck, R.P.G.; Labuschagne, C. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: A Sustainability Cost Accounting (SCA) procedure has been introduced that expresses the impacts on sustainable development associated with a developed technology, by means of a common financial denominator. This paper uses a case study to demonstrate and assess the SCA procedure, which considers the construction and operation of a hypothetical Gas-to-Liquid (GTL) fuelmanufacturing facility at a specific location in South Africa. The SCA indicators show that the negative environmental impacts associated with the GTL technology outweigh the internal economic benefits for the company. However, a net positive social benefit is associated with the technology, which decision-makers should consider with respect of the overall sustainability of the technology. Certain limitations of the SCA procedure are highlighted, and recommendations are made to develop such a methodology further. AFRIKAANSE OPSOMMING: